PALLIATIVE AND END OF LIFE CARE IN PRISONS IN ENGLAND AND WALES: DO INEQUALITIES EXIST? A SURVEY OF HEALTHCARE MANAGERS. Issue 1 (1st March 2013) - Fletcher, A J; Payne, S; Waterman, D; Turner, M
Abstract : Introduction: The End of Life Care Strategy (2008) states: 'high quality services should be available in all locations, including prisons'. Prisons have characteristics which potentially create inequalities in the delivery of care. A paucity of research means that the need for palliative and end of life care in prisons has not been established. Aims and Methods: To quantify palliative and end of life care need, in adult prisons and identify strategies for enhancing care. A self-reported questionnaire was developed and distributed to 124 prisons. Results: Data obtained from 39 prisons (31.5% response rate), revealed that between 2010–2012, 68 prisoners required palliative care, 45 were considered for release to receive care in alternative locations, of which 20 were released. Factors preventing release included ongoing risk, failure to identify patients in a timely manner, and prisoners' wishes to remain in prison. Two-thirds of prisons had a palliative care policy; 28% had implemented the Gold Standards Framework; 54% the Liverpool Care Pathway or equivalent and 36% Advance Care Planning. Ninety percent of prisons had access to palliative care nurse specialists and 77% palliative medicine consultants. Conclusions: The number of prisoners requiring palliative care is larger than expected. Although there is evidence of palliative care support and principles available, work is still required to ensure equity in end of life care provision for prisoners. Further research in this area, funded by Marie Curie Cancer Care, will begin in 2013.